2015
DOI: 10.1246/bcsj.20150110
|View full text |Cite
|
Sign up to set email alerts
|

Ligand-Hole in [SnI6] Unit and Origin of Band Gap in Photovoltaic Perovskite Variant Cs2SnI6

Abstract: Lead halide perovskites invoked new development research in the third-generation photovoltaics because of the high power conversion efficiencies (PCEs) of those photovoltaic cells as high as 20.1%. 16 These compounds are represented by the general chemical formula ABX 3 (A = Cs, CH 3 NH 3 , or CH 2 NH=CH; B = Pb or Sn; X = I, Br, or Cl), where the A cations are located in the cubic network of corner-sharing [BX 6

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
109
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 145 publications
(132 citation statements)
references
References 26 publications
21
109
2
Order By: Relevance
“…Among the many A 2 BX 6 compounds, [96][97][98][99] A 2 SnI 6 (A = Cs, MA), [100][101][102][103][104][105][106][107][108][109] Cs 2 PdBr 6 , [110,111] and Cs 2 TiBr 6 [112,113] have been investigated for photovoltaic applications. As the [BX 6 ] octahedra in A 2 BX 6 compounds are isolated, the optoelectronic properties of these compounds are rather different from those of 3D ABX 3 (B = Pb, Sn, and Ge) halide perovskites.…”
Section: D a 2 B(iv)x 6 Perovskite Variantsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the many A 2 BX 6 compounds, [96][97][98][99] A 2 SnI 6 (A = Cs, MA), [100][101][102][103][104][105][106][107][108][109] Cs 2 PdBr 6 , [110,111] and Cs 2 TiBr 6 [112,113] have been investigated for photovoltaic applications. As the [BX 6 ] octahedra in A 2 BX 6 compounds are isolated, the optoelectronic properties of these compounds are rather different from those of 3D ABX 3 (B = Pb, Sn, and Ge) halide perovskites.…”
Section: D a 2 B(iv)x 6 Perovskite Variantsmentioning
confidence: 99%
“…This leads to rather large m h for these compounds, particularly, along the Γ−X direction. [101] However, the transition from the VBM to the CBM is dipole-forbidden. Despite the isolation of [BX 6 ] octahedra, the CBMs are relatively dispersive, due to the charge redistribution of the B cations.…”
Section: D a 2 B(iv)x 6 Perovskite Variantsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, Cs2SnI6 have not shown p-type conductivity unlike the other Sn 2+ -based compounds and have shown ntype conduction or insulating behavior depending on the synthetic routes. Lee et al 13 reported the native n-type conduction with electron density (n) of ~110 14 cm 3 in polycrystalline Cs2SnI6 pellets annealed at 200 o C, while Zhang et al 18 observed very high resistivity in room temperature-processed Cs2SnI6. Therefore, in order to clarify the intrinsic nature of Cs2SnI6 and its origin, a systematic theoretical study on the intrinsic defects is important, which will provide a guiding principle for tuning its properties for photovoltaic and other semiconductor applications.…”
Section: +mentioning
confidence: 99%
“…The examples includes h-BN, MoS 2 (Figures 3b and 3c). 113116 The yields of product using this route are high and yields over 90% for MoS 2 and TaS 2 nanosheets have been reported.…”
mentioning
confidence: 99%